THE STAGES OF THE PRACTIC STATE REGULATION OF AGRICULTURAL PRODUCTION - I. Papakhchyan (Вестник университета)
Discusses stages of the system formation of state regulation of AIC, given their characteristics. Shows the limits of state rule regulation with legal, budgetary, tax, social, environmental parameters. It is noted that the regulation involving the state is divided into direct and indirect or economic and administrative tools. Allocated area of work in which the use of administrative methods is a necessary condition for balanced development of agriculture. Amount them, the author attributed the monopoly markets, the scope of non-reproducible resources, the environment, ecology, standard of living of the rural population.